PENGARUH INTEGRITAS DAN PENGALAMAN KERJA AUDITOR TERHADAP KUALITAS AUDIT PADA PT BANK MUAMALAT INDONESIA - Budi gautama Siregar; Maskota Harahap; Ali Hardana (Jurnal Mahasiswa Akuntansi Samudra, 2024)
This study aims to examine the influence of auditor integrity and work experience on audit quality. Integrity is an essential component of the auditing profession that can affect the quality of audit reports. In addition, auditor work experience is often considered a factor that determines the auditor's ability to perform their audit duties effectively. The research data was obtained through questionnaires distributed via Google Forms to 12 auditors at PT. Bank Muamalat Indonesia throughout Sumatera. The data was analyzed using multiple linear regression. The results of the study indicate that auditor integrity has a positive and significant impact on audit quality. Auditors with high levels of integrity tend to produce higher-quality audits because they adhere to professional ethical principles. On the other hand, auditor work experience does not have a significant effect on audit quality. Although experience is believed to enhance technical skills, this study found that work experience does not always correlate with the quality of the resulting audit. These findings emphasize the importance of integrity in the auditing profession and suggest that work experience alone is not sufficient to ensure audit quality. Therefore, auditing institutions should focus on the development of auditor ethics and integrity, in addition to providing adequate technical training. The study also recommends further research to explore other factors that may influence audit quality, such as continuous training and the adoption of modern audit technologies.